Shakespeare’s Bookish Rulers: Philosophy and Nature Poetry in the Henry VI Trilogy and The Tempest - Farkas, Aviva (Religions, 2023)
Shakespeare’s early Henry VI trilogy and late The Tempest both feature reclusive, bookish rulers who are deposed because their rivals perceive an opportunity in the rulers’ trustingness and lack of interest in political affairs. Furthermore, the deposed rulers also share an interest in Platonic philosophies of the Renaissance; they differ, however, in their respective preferences for particular Platonist authors and writings. Henry VI is devoted to Boethius’s The Consolation of Philosophy. While Prospero, the protagonist of The Tempest, may have focused on Boethius and similar authors when he was in Milan, by the time we meet him on his island, he prefers Neoplatonic magic, bequeathed to the Renaissance by Ficino. While the two stories are not often read together, I argue that doing so yields a fascinating contrast in the modes of existence dictated by different streams of Renaissance philosophical thought. While Henry VI’s credulity and Boethianism lead him to express a preference for a contemplative life and to adopt an attitude of extreme passivity and surrender, Prospero’s suspicion and powerful use of magic associate him with the active life. The ultimate expressions of Henry’s preference for the contemplative life and of Prospero’s association with the active life both involve nature poetry. Henry expresses yearning for the peaceful lifestyle of a shepherd in a pastoral lyric he delivers in 3 Henry VI, while Prospero celebrates human labor and achievement in a georgic masque which he produces.